Motives of physically active adults to participate in the 5 PKO Wroclaw Night Half Marathon - Stodółka, Weronika; Filipowski, Damian; Kosa, Jerzy; Stodółka, Jacek (Journal of Education, Health and Sport, 2017)
Introduction and aim: Running has become an integral part of social life around the world. It is the simplest and most natural form of movement, which is the basis of human existence. The popularity of this physical activity is increasing rapidly due to many sports and recreational events which are being more frequently organized. In Poland, long-distance running events are held, not only in big cities, but also in small towns and villages. Being by nature a “social animal”, people feel pressure from their environment to participate in such events. Thus, what motivates them to frequently make extreme physical effort? Materials and methods: The research group was comprised of 450 runners from all over Poland (331 men, 119 women). Diagnostic survey techniques and a questionnaire were used in the study. Results: Nearly one-third of the respondents declared their willingness to participate and complete another half marathon (29.11%). Only 28 people wanted to become champions in their age group, and another 23 subjects wanted a prize sponsored by an employer or other organization interested in their participation in a run. More than half of the respondents replied that participation in the half marathon was the result of many months of leading a healthy lifestyle. Conclusions: Participation in a half marathon allows competitors to fight their weaknesses. Runners want to participate in sports events because of the atmosphere and opportunity to spend time with their loved ones.